Estimation of greenhouse gas (GHG) emission and energy use efficiency (EUE) analysis in rainfed canola production (case study: Golestan province, Iran). (1st December 2016) - Kazemi, Hossein; Bourkheili, Saeid Hassanpour; Kamkar, Behnam; Soltani, Afshin; Gharanjic, Kambiz; Nazari, Noor Mohammad
Abstract: Increasing the use of energy inputs in agricultural section has been led to numerous environmental concerns such as greenhouse gas (GHG) emissions, high consumption of non-renewable resources, loss of biodiversity and environment pollutions. The study was aimed to analyze the energy use efficiency (EUE) and estimation of GHG emissions from rainfed–based canola production systems (RCPSs) in Iran. In this study, data were collected from 35 farms in Golestan province (northeast of Iran) by a face to face questionnaire performed and statistical yearbooks of 2014. The amount of GHG emissions (per hectare) from inputs used in RCPSs was calculated using CO2 emissions coefficient of agricultural inputs. Results showed that the EUE and net energy (NE) were as 3.44 and 35, 537.81 MJ ha −1, respectively. The value of these indices for the study area indicated that surveyed fields are approximately efficient in the use of energy for canola production. The highest share of energy consumption belonged to nitrogen fertilizer (42.09%) followed by diesel fuel (39.81%). In production of rainfed canola, GHG emission was estimated as 1009.91 kg CO2 equivalent per hectare. Based on the results, nitrogen fertilizer (44.15%), diesel fuel (30.16%) and machinery (14.49%) for field operations had the highest share of GHG emission. The total consumed energy by inputs could be classified as direct energy (40.09%), and indirect energy (59.91%) or renewable energy (2.02%) and nonrenewable energy (97.98%). These results demonstrate that the share of renewable energies in canola production is very low in the studied region and agriculture in Iran is very much dependent on non-renewable energies. In this study, the energy use status in RCPSs has analyzed and the main involved causes have been interpreted. Highlights: Fertilizers had the highest share in GHG emission. The share of renewable energy was low in canola production. Canola production is efficient in Iran.